Thermal and seismic performance evaluation of the innovative cylindrical RBS connection using numerical modelling. (April 2023) - Khalilpourazar, Yasaman; Lotfollahi Yaghin, Mohammad ali; Maleki, Ahmad
Abstract: Ductile connections have remarkably influenced the structural response during a fire or earthquake and prevented brittle failure. In this paper, an RBS connection with a robust cylindrical assembly is proposed and simulated by using the finite element program ABAQUS. The cylindrical RBS connection is made by cutting the continuous web and flange of the beam and replacing these parts with horizontal and vertical cylinders at the reduced region. Models with variable thickness and inner radius are subjected to thermal and seismic loading separately to assess failure mechanisms and plastic hinge formation. Based on the numerical results, the cylindrical RBS connection not only provides suitable ductility to overcome the fire-induced axial force but also exhibits a larger hysteretic enclosed area without lateral-torsional buckling under cyclic loading.